The effect of Sharia monetary policy instruments and Islamic bank financing on economic growth and inflation - Winarto, Fuad Hawari; Beik, Irfan Syauqi (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study aims to determine the influence of Open Market Operations (Sertifikat Bank Indonesia Syariah, SBIS), Sukuk of Bank Indonesia (Sukuk Bank Indonesia, SukBI), Bank Indonesia Sharia Deposit Facility (Fasilitas Simpanan Bank Indonesia, FASBIS), Islamic Interbank Money Market (IIMM/Pasar Uang Antar Bank Syariah, PUAS), and Islamic Bank Financing on economic growth and inflation in Indonesia. Methodology – This study uses the Vector Error Correction Model (VECM), which uses monthly data from January 2017 to December 2022. Findings – The results of the VECM analysis show that, in the short and long term, the FASBIS and PUAS variables significantly affect economic growth. The Covid-19 pandemic has a significant effect in the short term, whereas Islamic Bank Financing has a significant effect in the long term. In the Inflation model, only FASBIS has a significant short-term effect. In the long-term, FASBIS, PUAS, and Islamic Bank Financing significantly affect inflation. Implications – The results of this research suggest that the Government and Bank Indonesia will need to re-evaluate Sharia Open Market Operations, especially SBIS and SukBI instruments. This is the impact of the estimation results on the Open Market Operation variable, which are not significant, and the IRF results, which are negative in the Economic Growth Model and positive in the Inflation Model, indicating that the Open Market Operation variable actually inhibits economic growth and triggers inflation. Originality – This study discusses the influence of Sharia monetary instruments before and after the Covid-19 pandemic and adds the SukBI instrument as a Sharia monetary instrument.